PENGARUH ANALISIS JABATAN DAN DESAIN PEKERJAAN TERHADAP PERENCANAAN SDM PADA DINAS KEPEMUDAAN, OLAHRAGA DAN PARIWIISATA KABUPATEN BANYUASIN - Suhada Suhada; Ninin Non Ayu Salmah; Tri Oktavia (STMIK Pringsewu, 2023)
His study aims to determine the effect of Job Analysis and Job Design partially or simultaneously on HR Planning at the Youth and Sports Office of Banyuasin Regency. The population of this research is all employees, totaling 108 people at the Youth and Sports Office of Banyuasin Regency. The sample in this study amounted to 31 civil servants. The data analysis technique in this study is multiple linear regression and the coefficient of determination (R2) The results of this study indicate that: 1) Based on the hypothesis test of the F test, the variables of job analysis and job design on HR planning show a significant value of 0.457 0.05, meaning that simultaneously job analysis and job design have no significant effect on HR planning. 2) Based on the hypothesis test, the t-test variable Position Analysis on HR planning shows a significant value of 0.327 0.05, meaning that partially Job Analysis has no significant effect on HR Planning. 3) Based on the hypothesis test, the t-test of the Job Design variable on HR Planning shows a significant value of 0.444 0.05, meaning that partially the Job Design variable has no significant effect on HR Planning.